Characterization and evaluation of the variability of dragon fruit accessions in Dairi District, North Sumatra Province, Indonesia - Luthfi Aziz Mahmud Siregar; NINA UNZILA ANGKAT; REVANDY ISKANDAR DAMANIK (Nusantara Bioscience, 2021)
Abstract. Siregar LAM, Angkat NU, Damanik RI. 2021. Characterization and evaluation of the variability of dragon fruit accessions in Dairi District, North Sumatra Province, Indonesia. Nusantara Bioscience 13: 138-145. Many types of dragon fruits were planted in Dairi District of North Sumatra Province without much information of their importance in economic values. Therefore, this study was carried out to evaluate the variability of the dragon fruit population in this region to assist the local farmers in selecting the best species for planting. This study used a morphological observation method based on dragon fruit descriptor employing a purposive sampling technique. A total of 56 dragon fruit accessions collected from Sidikalang, Sitinjo, and Siempat Nempuhulu Sub-districts were studied and characterized based on the morphological characteristics of stems, flowers, and fruit. The results showed some variations in the stem, flower, and fruit morphology among the studied population. The dragon fruit plant that is widely cultivated by farmers in three sub-districts of Dairi District is a species of Hylocereus polyrhizus. Phenotypic diversity analysis showed seven quantitative characters with broad criteria of eighteen characters observed, namely stem length, pericarpel length, number of lobes, flower shoot length, number of bractea, bractea peak length, and fruit weight. However, phenotypic diversity analysis indicates they are closely related to each other except for accession D17 the red dragon fruit or red pitaya (Hylocereus spp.), and it could be the exotic species for nation-wide planting in Indonesia.